[tex]~~~~~~\textit{vertical parabola vertex form} \\\\ y=a(x- h)^2+ k\qquad \begin{cases} \stackrel{vertex}{(h,k)}\\\\ \stackrel{"a"~is~negative}{op ens~\cap}\qquad \stackrel{"a"~is~positive}{op ens~\cup} \end{cases} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \stackrel{vertex}{(-3~~,~~5)}\qquad y=a[x-(-3)]^2+5\implies y=a(x+3)^2+5 \\\\\\ \textit{we also know that} \begin{cases} x=-1\\ y=2 \end{cases}\qquad 2=a(-1+3)^2+5\implies -3=a(2)^2 \\\\\\ -3=4a\implies -\cfrac{3}{4}=a~\hfill \boxed{y=-\cfrac{3}{4}(x+3)^2+5}[/tex]